The Effect of Dynamic Marketing Capabilities on Organizational Reputation: An Analytical Research in General Company Diyala - Abd Abbas Al-Salhi, Souad; Saeed Abbas Al-Jawfi, Alia (Journal of Economics and Administrative Sciences, 2024)
The current research aims to determine the extent of the impact of dynamic marketing capabilities in its dimensions (product development, market knowledge, customer relationship management) as an explanatory variable on organizational reputation in its dimensions (social responsibility, service quality, creativity) as a response variable to arrive at appropriate mechanisms that enable General Diyala Company  By exploiting its dynamic marketing capabilities to achieve its organizational reputation. For this purpose, several hypotheses formulated, the most important of which is finding the influence relationship. To test the research hypotheses, the researcher chose Diyala Company, and relied on the descriptive-analytical method. Data collected from  various levels of management and departments. The data included managers, agents, marketing, media, communications, and relations departments. The sample number was (115) individuals, and the questionnaire was relied upon to collect data, in addition to the researcher's use of personal interviews with the company's general manager and department managers to enhance the questionnaire's results. The researcher relied on SPSS, Amos, and Excel programs to process and analyze the questionnaires. He also used descriptive statistics methods (arithmetic mean, standard deviation, coefficient of variation, coefficient of determination, R2, relative importance), and the most prominent conclusions were the interest in creative people and the adoption of rules and instructions that suit their needs and skills, which reflects a strategic vision to support and encourage creativity within the company.Research paper.